Obesity Current Research and Future Hope - Rehan Haider; Asghar Mehdi; Geetha Kumari (Contemporary Journal of Applied Sciences, 2024)
Obesity is a broad-based public health issue that is defined by excessive consumption of body fat, which is associated with more negative health impacts than positive ones, such as diabetes, cancer, and cardiovascular disease. This abstract backs up a brief overview of the approaches being used in the fight against obesity today and in the future.The goal of current research efforts is to comprehend the intricate interplay of behavioral, environmental, and historical factors that contribute to corpulence. Genetic research has uncovered a large number of vulnerable genes, removing the inherited components of obesity. In the meanwhile, material factors like fattening diets and indolent habits warrant more study.Approaches to behavior qualification and novel healing attacks are being energetically investigated. Strategies include expanding anti-corpulence medications, bariatric surgery, and targeting gut bacteria. In the areas of precision, treatment, customized digestive approvals, plant structure, and customized absorption, encouraging results are emerging.The integration of scientific and mathematical strength techniques holds the key to future success in the battle against obesity. Innovative approaches to tracking and managing obesity are provided by wearable technology, mobile devices, and telehealth manifestos. Healthcare providers and situations can benefit from the large dossier science of logical analysis and artificial intelligence in generating thoughtful remedies for individualized burden administration